Performance analysis of a low capacity solar tower water heating system in climate of Pakistan - Ali, M. (Elsevier Ltd, 2017)
The heating demands are currently fulfilled through conventional technologies based on fossil fuels. However, due to rapid depletion and environmental hazards of fossil fuels, the focus has shifted to harness the heat energy from renewable energy resources such as solar energy. In general, flat plate and evacuated tubes collectors are used for water heating yet there is another technology known as solar thermal tower (STT) which can be used for heating applications. The current study is focussed on real time performance analysis of solar thermal tower water heating system under climate conditions of Taxila, Pakistan. Initially, a mathematical model is developed to design a small capacity solar thermal tower system. The system is simulated using MATLAB for five different climate conditions of Pakistan i.e. Peshawar, Taxila, Multan, Karachi, and Lahore for potential assessment. Afterwards, an experimental setup is developed at Taxila consisting of a cavity type receiver made of stainless tubes, heliostats made of mirror and complete instrumentation for data measurements. The performance analysis is presented in terms of temperature difference (ΔT), absorbed heat (Qabs), and efficiency (η) with fixed and variable positions of heliostats for 12 selected days between September and February. The results showed that the maximum temperature difference with fixed heliostats position was 3 °C, Qabs was 27 W and the maximum efficiency was 30. However, with variable heliostats positions, the maximum value of temperature difference achieved was 16 °C that resulted Qabs 170 W and efficiency 34. Finally, a reasonable agreement between simulated and experimental results was obtained for climate conditions of Taxila. © 2017 Elsevier B.V.